Characterization of long-wavelength semiconductor lasers - Fawwaz Mohd Noor (2015)
Quantum cascade laser (QCL) is a unipolar laser diode with intersubband transitions within heterostructural forms. It garnered much attention from the semiconductor laser community due to its efficacy in performing even at low temperatures. As a result, there can be many significant applications that can be derived from it. QCL performance follows a complex sequence of steps, thus requiring meticulous measurements of the numerous spectral and electrical characteristics of laser devices. In this project, the author focuses on research for electrical and optical characterization of high performance ridge waveguide mid-infrared (~3-20um) and terahertz (~300-10 THz) QCLs. The author will also explain the working principle of the equipments that are commonly used for characterisation. In addition, the author performed research on uses of LabVIEW and the ways to link hardware to the computer. Thereafter, the author modified a LabVIEW driver to interface with hardware for future characterisation work. The project will first explore a literature review on the progression of QCLs, factors for characterisation of them, and their applications. The project will then set out with a simple experiment and interface the LabVIEW programme with the hardware, and report test results. Finally, the report will end with challenges encountered and recommendations for future work.